Contribution of Village Government and its Impact on Maternal and Child Health in Medan Estate Village, Percut Sei Tua District - Simbolon, Nur Anisa; Samura, Laras Hilda; Sembiring, Vanessa Uli; Sembiring, Dian Wahyu Harmoni; Ivanna, Julia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This study aims to review the contribution of village government and its impact on maternal and child health in Medan Estate Village, Percut Sei Tua District. The research method used is a qualitative approach. The study used data collection techniques through observation, interviews, and documentation. The success of improving the quality of public services reflects good government performance. The results of the research obtained are, in implementing public service improvement programs, the Medan Estate village government implements several programs such as maternal and child health programs through posyandu. The program includes the distribution of KTP (beans, eggs, bananas) which is given every month to children under five while for pregnant women and the elderly it is given every 3 months and providing spiritual understanding to prospective brides.